Internal Morphology and Phylogenetic Position of Mycetomorpha vancouverensis (Pancrustacea: Rhizocephala), an Enigmatic Parasitic Barnacle - Aleksei Miroliubov; Anastasia Lianguzova; Darya Krupenko; Liudmila Poliushkevich; Semyon Novokreshchennykh; Natalia Arbuzova; Georgii Kremnev (Biology)
Mycetomorpha vancouverensis is an enigmatic parasitic barnacle from the family Mycetomorphidae, known for its unclear phylogenetic position within Rhizocephala. Specimens of M. vancouverensis were collected from infected Neocrangon communis shrimps near the South Kuril Islands. Detailed morphological studies were conducted using histological techniques and scanning electron microscopy, and 18S rDNA sequences were used to resolve the phylogenetic position of M. vancouverensis within Rhizocephala. Morphological analysis revealed a complex externa structure with spermatogenic bodies and the presence of a main trunk in the interna. Some of the side branches of the interna invade the host’s nerve tissue and are modified into specialized goblet-shaped organs. These invasive rootlets are morphologically similar to the goblet-shaped organs in the family Peltogastridae. Molecular analysis confirmed that the Mycetomorphidae is a sister group to the Peltogastridae. At the same time, peltogastrids were recovered as polyphyletic. Our findings contribute to the understanding of the evolution of parasitic barnacles and highlight the unique adaptations of Mycetomorphidae within the broader context of Rhizocephala.